Voting Rights Position in Constitutional Review and Human Rights - Jamaluddin, Jamaluddin (International Journal Labs, 2021)
Law is an important instrument in protecting and upholding human rights in the state. In protecting and ensuring the enforcement of human rights in the state, it must be ensured that the law becomes an instrument in monitoring and even restricting public or state authorities so that there is no abuse of power, in many cases being the beginning of human rights violations. This research aims to examine and analyze the protection of human rights in the Indonesian Constitutional Law Post Amendment to the 1945 Constitution. This research uses normative legal research methods or literature studies, with materials in the form of secondary and tertiary legal materials. The main law material is the 1945 Constitution of the Republic of Indonesia while the secondary material is legal literature that explains and analyzes the laws and regulations related to this research. The result of this research is that the right to vote is contained in various legal provisions, both international and national. Persons with disabilities, as part of Indonesian citizens are also entitled to be actively involved in political life in accordance with Article 21 of the Universal Declaration of Human Rights, Article 25 of the Civil Rights Covenant, Article 28D paragraph (3), Article 28H Paragraph (2) and Article 28I Paragraph (2) the 1945 Constitution after the amendments and Article 43 Paragraphs (1) and (2) of Law no. 39/1999 on Human Rights emphasizes that every citizen has the right to get equal opportunities in government, both to be elected and to vote without discrimination.